Self-concept of EFL preservice teachers as reflected in their teaching performance - Dina Rachmawati (Indonesian Journal of Applied Linguistics, 2022)
A number of studies discussing the significant role of self-concept in the educational field are evident.  However, research investigating the self-concept of English as a Foreign Language (EFL) preservice teachers and how the self-concept is reflected in the teaching performance is limited. Thus, this study was aimed at investigating the portrait of the self-concept of English preservice teachers in the Indonesian context and how the self-concept is reflected in their teaching performance. A qualitative research paradigm, especially an explanatory case study design was employed to figure them out. The study found that first, diverse portraits of self-concept i.e. highly positive, moderate, and low or negative self-concept were captured in the participants’ academic self-concept (pedagogic and professional self-concept) with the inclination of higher portrayal in the non-academic sub-aspects of self-concept (social and emotional self-concept). Second, the congruent and incongruent reflection of self-concept were identified. The findings imply that academic aspects of self-concept (pedagogic and professional competence) seem to be contributing factors to the participants’ negative self-perception of their self-concept. Moreover, reflexivity, internal and external frames of reference, and emotion regulation strategies seem to be contributing factors to the construction of the participants’ self-concept. This study concludes that the construction of the participants’ self-concept dynamic during the practicum and its manifestation in the teaching performance is affected by internal and external factors.